How do older adults understand and manage distress? A qualitative study - Alice Moult; Tom Kingstone; Carolyn A. Chew-Graham (BMC Family Practice, 2020)
Abstract Background Distress is an expected emotional response to a negative life event. Experiences common in later life may trigger distress such as bereavement or loss of physical mobility. Distress is considered to be distinct to anxiety and/or depression and is not diagnostically labelled as a mental health problem. Older adults will often manage their own distress. Previous literature has focused on how younger adults self-manage mental health problems, however little research has explored the self-management strategies used by older people. There is a need to clarify the role of primary care in the context of distressed older adults who may consult healthcare services. This study seeks to address these gaps through qualitative methods. Methods Keele University’s ethical review panel approved this study. We recruited older adults who self-identified as distressed from community groups in North Staffordshire, England. Data were generated through semi-structured interviews and analysed thematically using constant comparison methods. A patient and public involvement and engagement group contributed to development of the research questions and methods, and offered their perspectives on the findings. Results After 18 interviews data saturation was achieved. Key themes were: experiences of distress, actions taken, help-seeking from healthcare services and perceptions of treatments offered in primary care. Various forms of loss contributed to participants’ distress. Participants initiated their own self-management strategies which included: pursuing independent activities, seeking social support and attending community groups and church. Five participants reported having consulted a GP when distressed but described a lack of acceptable treatments offered. Conclusions To support older adults who are distressed, healthcare professionals in primary care should consider exploring how patients currently manage their mood problems, provide a broad range of information about potential management options and consider sign-posting older adults to community resources.